Synthesis and PET Imaging Biodistribution Studies of Radiolabeled Iododiflunisal, a Transthyretin Tetramer Stabilizer, Candidate Drug for Alzheimer’s Disease - Joshi, Sameer M.; Wilson, Thomas C.; Li, Zibo; Preshlock, Sean; Gómez-Vallejo, Vanessa; Gouverneur, Véronique; Llop, Jordi; Arsequell, Gemma (Molecules (Basel, Switzerland), 2024)
The small-molecule iododiflunisal (IDIF) is a transthyretin (TTR) tetramer stabilizer and acts as a chaperone of the TTR-Amyloid beta interaction. Oral administration of IDIF improves Alzheimer’s Disease (AD)-like pathology in mice, although the mechanism of action and pharmacokinetics remain unknown. Radiolabeling IDIF with positron or gamma emitters may aid in the in vivo evaluation of IDIF using non-invasive nuclear imaging techniques. In this work, we report an isotopic exchange reaction to obtain IDIF radiolabeled with 18F. [19F/18F]exchange reaction over IDIF in dimethyl sulfoxide at 160 °C resulted in the formation of [18F]IDIF in 7 ± 3% radiochemical yield in a 20 min reaction time, with a final radiochemical purity of >99%. Biodistribution studies after intravenous administration of [18F]IDIF in wild-type mice using positron emission tomography (PET) imaging showed capacity to cross the blood-brain barrier (ca. 1% of injected dose per gram of tissue in the brain at t > 10 min post administration), rapid accumulation in the liver, long circulation time, and progressive elimination via urine. Our results open opportunities for future studies in larger animal species or human subjects.